Land use cover changes abated terrestrial ecosystem carbon sink in China during the past four decades - Xueqing Jiang; Jinxun Liu; Changhui Peng; Huai Chen; Le Wang; Dongxue Yu; Qiuan Zhu (All Earth)
Changes in land use and cover can strongly affect terrestrial carbon balance, which in turn can affect the calculation of carbon sinks that will keep future temperature within desired limits. Understanding how changes in land use and cover influence carbon sinks is challenging. Here, we simulated net carbon balance across China with full consideration of land use and land cover between 1981 and 2020 using the dynamic global vegetation model. The results indicated that carbon sink of terrestrial ecosystem in China have grown steadily particularly since 2001, the average values of the net primary productivity, net ecosystem productivity and net biome productivity were 3317 TgC • yr−1, 325 TgC • yr−1 and 70 TgC • yr−1. However, during the period, changes in land use and cover cumulatively reduced net primary productivity by 1,353.00 TgC, net ecosystem productivity by 1,290.71 TgC and net biome productivity by 226.93 TgC. Land use and cover changes have created a carbon source effect which abated terrestrial ecosystem carbon sink in China since 1981. Our findings may help guide policies to regulate land use in order to help China achieve carbon neutrality in the future.